Geology of Batu Melintang – Jeli, with focus on high grade metamorphism and Migmatite - BIN YAACOB, AHMAD ZAKIRI (Universiti Teknologi PETRONAS, 2015)
The area of Batu Melintang, Jeli is covered by mostly metamorphic and igneous rocks with some occurrences of late phase intrusions such as dykes, which are mainly quartz and quarzo-feldsphatic dykes. The factors affect the metamorphism grade that occurs to the specific region, such as the temperature and the pressure. The main objective of this study is to understand more on the metamorphism and its relation with the occurrences of migmatite in term of rheology, temperature and pressure in accordance to Barrovian metamorphism. Meanwhile, the spectacular migmatitic outcrops expose in Politeknik Jeli shows a real mixture of metamorphic and igneous rocks due to incomplete anatexis process, or the transition between metamorphic and igneous domains. It shows a metamorphic texture, either macroscopic or microscopic, such as schistosity and mineral banding or segregation (leucosome and melanosome) that intermixed with medium- to coarse-grained granite.